STRATEGI MENGHADAPI KERAGUAN MASYARAKAT TERHADAP VAKSINASI COVID-19 BERDASARKAN 5C-FRAMEWORK - Susiani Endarwati; Lely Khulafa'ur R; Rahma Novita Asdary; Hengky Irawan (Universitas Kadiri, 2022)
ABSTRACTIn the midst of a significant increase in positive cases of Covid-19, vaccination is Indonesia's way to keep the number from the increasing spread of Covid-19 infections. The launch of the acceleration of vaccines that are also being assisted by the TNI and POLRI is hampered by fear, doubt or refusal to be vaccinated by certain communities or groups. Explore the level of doubt and confidence of vaccination target participants based on the 5C framework: confidence (confidence), complacency (complacency), convenience / constraints (ease / constraints), calculation of risk (calculation of risk), and collective responsibility (group responsibility)). This vaccination activity is carried out simultaneously, with the target of ± 800 doses every week starting from August to December 2021 in the Kediri Kota Sector Police Work area, in the framework of the Semeru Merdeka Vaccination. The widely used research framework shows that there are five main determinants, the individual's level of doubt about vaccination: trust, satisfaction, ease (or constraints), risk calculation, and group responsibility. The majority of people present at the Merdeka Semeru vaccination site in the kediri city police station showed confidence in health workers, satisfied with the provided.Keywords : vaccination,Covid-19,Polri,Vaccine hesitancy,5c-frameworkABSTRAK Di tengah peningkatan signifikan kasus positif Covid-19, vaksinasi menjadi cara Indonesia untuk menjaga jumlah dari semakin merebaknya infeksi Covid-19. Peluncuran percepatan vaksin yang juga tengah dibantu oleh TNI dan POLRI terhambat oleh rasa takut, keraguan atau penolakan untuk divaksinasi oleh komunitas atau kelompok tertentu. Menggali tingkat keraguan dan kepercayaan peserta sasaran vaksinasi berdasarkan kerangka 5C: confidence (kepercayaan), complacency (kepuasan diri), convenience/constraints (kemudahan/kendala), calculation of risk (perhitungan terhadap risiko), dan collective responsibility (tanggung jawab kelompok)). Kegiatan vaksinasi ini dilakukan secara simultan, dengan sasaran ± 800 dosis setiap minggunya dimulai bulan Agustus sampai dengan Desember 2021 di wilayah Kerja Kepolisian Sektor Kediri Kota, dalam rangka Vaksinasi Merdeka Semeru. Kerangka penelitian yang banyak digunakan menunjukkan bahwa ada lima faktor penentu utama, level individu mengenai keraguan akan vaksinasi yakni: kepercayaan, kepuasan, kemudahan (atau kendala), perhitungan risiko, dan tanggung jawab kelompok. Mayoritas masyarakat yang hadir di lokasi vaksinasi Merdeka Semeru wilayah kerja Polres Kota Kediri menunjukkan rasa percaya terhadap tenaga kesehatan, puas akan layanan yang diberikan,Kata Kunci:Vaksinasi,Covid-19,Polri,Vaccine hesitancy,5c-framework